O ensino de filosofia e o bullying: entre o currículo e as aulas - Maia, André Augusto (Universidade Federal de São Carlos, 2019)
This dissertation, entitled "Philosophy Teaching and Bullying: what is between the Curriculum and the classes", presents a study conducted in a state public school in Ribeirão Preto, city in the State of São Paulo. The aim of this work was to investigate how theoretical subsidy present in the curriculum of philosophy teaching can help to fight bullying practices in the school environment. The student edification, through the Philosophy state curriculum, needs to be an instance of the proposition of reflection situations and the problematization of the challenges of daily school life. The methodology used comprised a bibliographical study of works and critiques about the curriculum problematic, as well as the philosophical foundation through thought of Critical Theory, especially by of the Theodor Adorno contribution. The method of approach in school was given by proposing an intervention project with students who were bullied as well as the other students of the school, through workshops and philosophical experiences.
Philosophy teaching and bullying: what is between the curriculum and the classes
Keywords: Filosofia; Ensino; Currículo; Teoria crítica; Bullying; Preconceito; Philosophy; Teaching; Curriculum; Critical theory; Preconception; CIENCIAS HUMANAS::FILOSOFIA